Systematic review of mitochondrial dysfunction and oxidative stress in aging: a focus on neuromuscular junctions - Chai, Senlin; Zhang, Ning; Cui, Can; Bao, Zhengyuan; Wang, Qianjin; Lin, Wujian; Wong, Ronald Man Yeung; Law, Sheung Wai; Schönmehl, Rebecca; Brochhausen, Christoph; Cheung, Wing Hoi (Neural regeneration research, 2026)
Mitochondrial dysfunction and oxidative stress are widely regarded as primary drivers of aging and are associated with several neurodegenerative diseases. The degeneration of motor neurons during aging is a critical pathological factor contributing to the progression of sarcopenia. However, the morphological and functional changes in mitochondria and their interplay in the degeneration of the neuromuscular junction during aging remain poorly understood. A defined systematic search of the PubMed, Web of Science and Embase databases (last accessed on October 30, 2024) was conducted with search terms including ‘mitochondria’, ‘aging’ and ‘NMJ’. Clinical and preclinical studies of mitochondrial dysfunction and neuromuscular junction degeneration during aging. Twenty-seven studies were included in this systematic review. This systematic review provides a summary of morphological, functional and biological changes in neuromuscular junction, mitochondrial morphology, biosynthesis, respiratory chain function, and mitophagy during aging. We focus on the interactions and mechanisms underlying the relationship between mitochondria and neuromuscular junctions during aging. Aging is characterized by significant reductions in mitochondrial fusion/fission cycles, biosynthesis, and mitochondrial quality control, which may lead to neuromuscular junction dysfunction, denervation and poor physical performance. Motor nerve terminals that exhibit redox sensitivity are among the first to exhibit abnormalities, ultimately leading to an early decline in muscle strength through impaired neuromuscular junction transmission function. Parg coactivator 1 alpha is a crucial molecule that regulates mitochondrial biogenesis and modulates various pathways, including the mitochondrial respiratory chain, energy deficiency, oxidative stress, and inflammation. Mitochondrial dysfunction is correlated with neuromuscular junction denervation and acetylcholine receptor fragmentation, resulting in muscle atrophy and a decrease in strength during aging. Physical therapy, pharmacotherapy, and gene therapy can alleviate the structural degeneration and functional deterioration of neuromuscular junction by restoring mitochondrial function. Therefore, mitochondria are considered potential targets for preserving neuromuscular junction morphology and function during aging to treat sarcopenia.
Online veröffentlicht: 29. April 2025
Gesehen am 02.12.2025